A Review of the Quadratus Lumborum Block and ERAS - Akerman, Michael; Pejčić, Nada; Veličković, Ivan (Frontiers in Medicine, 2018)
The use of truncal nerve blocks have been described since 2001. Since then, there have been many studies trying to understand the ideal clinical scenarios for its use. Since 2001, the TAP block has evolved in many ways including from landmark based technique to ultrasound guided and more recently, into the Quadratus Lumborum (QL) block. Its anatomical placement, concentration of local anesthetic, volume of local anesthetic and anatomic placement have all been raised as clinical questions. This article will discuss the literature of the QL block in an effort to understand how it is best used in a variety of clinical scenarios.